Post-transcriptional mending of gene sequences: Looking under the hood of mitochondrial gene expression in diplonemids - Valach, Matus; Moreira, Sandrine; Faktorová, Drahomíra; Lukeš, Julius; Burger, Gertraud (RNA biology, 2016)
The instructions to make proteins and structural RNAs are laid down in gene sequences. Yet, in certain instances, these primary instructions need to be modified considerably during gene expression, most often at the transcript level. Here we review a case of massive post-transcriptional revisions via trans-splicing and RNA editing, a phenomenon occurring in mitochondria of a recently recognized protist group, the diplonemids. As of now, the various post-transcriptional steps have been cataloged in detail, but how these processes function is still unknown. Since genetic manipulation techniques such as gene replacement and RNA interference have not yet been established for these organisms, alternative strategies have to be deployed. Here, we discuss the experimental and bioinformatics approaches that promise to unravel the molecular machineries of trans-splicing and RNA editing in Diplonema mitochondria.
Keywords: Euglenozoa; Base Sequence; protozoální proteiny; diplonemids; posttranskripční úpravy RNA; RNA Editing; Mitochondria; RNA editing; trans-splicing; Cryptic genes; RNA, Transfer; Protozoan Proteins; mitochondriální proteiny; mitochondrie; regulace genové exprese; RNA Processing, Post-Transcriptional; multipartite mtDNA; editace RNA; RNA transferová; sekvence nukleotidů; Gene Expression Regulation; Mitochondrial Proteins; gene fragmentation